Health literate maternity care of forced migrant women in Germany - Elizabeth Mohr; Martha Engelhardt; Mathilde Gaudion; Razan Al Munjid; Anne-Sophie Krautstengel; Lisa Patzelt; Theda Borde (SSM: Qualitative Research in Health, 2023)
Understanding health literacy in maternity care of forced migrant women in Germany provides invaluable insights into the health literacy-related barriers forced migrant women face and the resources available to them. These are integral to building health literate maternity care, which is diversity-sensitive and responsive to forced migrant women's needs. This study conducted a secondary qualitative analysis of health care providers' perspectives on the role of health literacy in maternity care of forced migrant women in three federal states in Germany (North Rhine-Westphalia, Brandenburg, Berlin). 59 problem-centered interviews were analyzed using Framework Analysis and the European Health Literacy Survey's health literacy model. The model was revised to better reflect the dimensions and determinants of the forced migration context (e.g., the healthcare system was included as a determinant). The results showed that barriers and resources related to accessing, understanding, appraising, and applying information in maternity care were present throughout pregnancy until after birth. Barriers were predominantly at the healthcare level (e.g., lack of language interpreters) and situational level in encounters with health care providers (e.g., diversity sensitivity). The main resources were forced migrant women's digital networks and the mediating role of providers and their networks. The results made clear that health literate maternity care requires three main factors: diversity-sensitive health care providers and healthcare structures, involvement of forced migrant women in research and practice, and health literate communication. The study proposes an adapted model of health literacy, which could be applied in future research on health literacy and migration.